Influence of alumina feeding dose distribution on superheat based on computational simulation. (15th October 2020) - Zhu, Jiaming
In Hall-Héroult cell, alumina dissolution has minimum requirement for superheat, however the superheat may not be uniform because the heat dissipation at the end parts is obviously higher than the middle part, which leads to the lower temperature at the end parts. In this study, the influences of alumina feeding dose distribution on the alumina concentration and the bath temperature near the feeder were simulated in computational numerical simulation, and then several cases with different feeding dose distribution were assessed by comparing the superheat per unit feeding dose. Furthermore, a methodology was proposed to optimise the alumina feeding dose distribution. It shows that the cases with lower alumina feeding dose at the end parts have better superheat distribution than the cases with uniform alumina feeding dose distribution. The optimal one is the case with feeding dose distribution (1.6, 1.8, 2.0, 2.0, 1.8, 1.6 kg) of alumina.